Debt-Based Economy: A Reappraisal of Prosperity and Crisis - Furqani, Hafas; Fuad, Zaki; Idul Adha, Syamsul; Awalurramadhana, Awalurramadhana (International Journal of Economics and Financial Issues, 2023)
Debt and economic activity seem to be inseparable. Debt in a society is considered as something normal in economic activities to meet various needs. The government of a country also needs external debt to overcome the problem of budget deficit in addition to providing a greater stimulus to domestic economic growth. Debt has eventually become a lifestyle and is considered as a profitable business. Therefore, credit facilities have been innovated from a simple form aimed at assisting those in need into a sophisticated financial product aimed at commercialization and profit through financial engineering. In Islamic perspective, debt is allowed within certain Shari’ah and ethical parameters. It is acknowledged that debt have both advantages and disadvantages in the economy. Debt is viewed as both a driver of prosperity and a source of economic crisis. Therefore, this paper recommends that taking debts should be in line with the ability to repay, good management and use of debt for the right purpose. In addition, debt should be made transparent to the public in order to create senses of responsibility, instituting regulating framework of supervision, and embedding it in macroeconomic policies to stimulate growth and enhance welfare.